Advancing the use of organization theory in implementation science - Leeman, Jennifer (Prev Med, 2019)
Healthcare settings and systems have been slow to adopt and implement many effective cancer prevention and control interventions. Understanding the factors that determine successful implementation is essential to accelerating the translation of effective interventions into practice. Many scholars have studied the determinants of implementation, and much of this research has been guided by the Consolidated Framework for Implementation Research (CFIR). The CFIR categorizes implementation determinants at five levels (characteristics of the intervention, inner setting, individual, processes, and outer setting). Of these five levels, determinants at the level of the outer setting are the least developed. Extensive research in fields other than healthcare suggest that determinants at the level of the outer setting (e.g., funding streams, contracting practices, and public policy) play a central role in shaping when and how an organization implements new structures and practices. Thus, a more comprehensive understanding of outer-setting determinants is critical to efforts to accelerate the implementation of effective cancer control interventions. The Cancer Prevention and Control Research Network (CPCRN) created a cross-center workgroup to review organizational theories and begin to contribute to the creation of a future framework of constructs related to outer setting determinants. In this paper, we report findings from the review of three organizational theories: Institutional Theory, Transaction Cost Economics, and Contingency Theory. To demonstrate the applicability of this work to implementation science and practice, we have applied findings to three case studies of CPCRN researchers’ efforts to implement colorectal cancer screening interventions in Federally Qualified Health Centers.